PENDAMPINGAN PEMASARAN DENGAN DIGITAL MARKETING PRODUK SENI BUDAYA PADA UMKM DESA TULUSBESAR KABUPATEN MALANG - Palandi, Esther Hesline (Dharma: Jurnal Pengabdian Masyarakat, 2024)
This service activity was carried out to provide knowledge about marketing with digital marketing of arts and culture products by MSMEs in the Tulusbesar village community, Malang district. This activity will start from September to October 2023. This activity aims to increase community independence in running their business and achieving profits. The method for implementing marketing assistance with digital marketing is as follows: 1) Participants are given an understanding of the target market who is interested in arts and culture products; 2) The activity implementation team presents material according to the theme, creates attractive media content through product catalogues; 3) Participants carry out science, technology, social and culture simulations by recording orders and serving purchases through online shop applications on the Shopee and Tokopedia marketplaces; The implementation of this service with the digital marketing theme consisted of 4 art and culture craftsmen participants who already have micro or medium scale businesses. The results obtained from this activity are the implementation of knowledge, such as multimedia, e-commerce and entrepreneurship, thereby providing benefits to the SME community.